A Case of Ovarian Dysplasia and a Vaginal Fibroleiomyoma in a Young Golden Retriever - McCarter, Samantha; Sponenberg, D. Phillip; Saunders, Geoffrey; Cecere, Julie (Frontiers in Veterinary Science, 2021)
This case demonstrates a unique ovarian congenital anomaly that likely contributed to the development of a rare fibroleiomyoma in the cranial vagina of a young bitch. A 13 month old intact female Golden Retriever presented to the veterinary teaching hospital for urinary incontinence, hematuria, and persistent vaginal discharge. Physical examination revealed a mucopurulent serosanguinous malodorous vulvar discharge, and after further diagnostics was reclassified as persistent estrus. Abdominal palpation and ultrasound revealed uterine thickening and poorly visualized ovaries. The reproductive tract was removed during an ovariohysterectomy, revealing small ovaries and a white anterior vaginal mass. Histopathology revealed dysplastic ovaries with hyperplastic granulosa cells and a benign vaginal fibroleiomyoma. These morphologic changes are consistent with elevated estrogen levels. It was thus concluded that her persistent estrus and the fibroleiomyoma were both secondary to persistent estrogen production by the hyperplastic granulosa cells.